(n + 7)(n + 9) = ?

\(n^{2}+16 n+63\)

Explanation

When multiplying binomials use the FOIL method which has you multiply the First two terms in each binomial:
\( n \times n = {n^2}\)
Then multiply the Outside two terms in each binomial:
\(n \times 9=9 n\)
Then multiply the Inside two terms in each binomial:
\(7 \times n=7 n\)
Then multiply the Last two terms in each binomial:
\(7 \times 9=63\)
Then add all of those terms together to get the answer:
\( {n^2} + 9n + 7n + 63 = {n^2} + 16n + 63\)

Visit our website for other ASVAB topics now!